1996
DOI: 10.1097/00007890-199601270-00009
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Renal Artery Stenosis in 77 Patients-Does It Have an Immunological Cause?1

Abstract: Transplant renal artery stenosis (TRAS) is a common complication after transplantation and is an important cause of graft dysfunction. Damage from graft rejection, trauma, and atherosclerosis have been implicated as possible causes. We reviewed all 917 patients transplanted in our unit since 1978 to study the prevalence, clinical features, and possible causes of TRAS. Seventy-seven patients with TRAS were identified. The detected incidence was 2.4% before the introduction of color doppler ultrasonography (CDU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 11 publications
5
75
0
5
Order By: Relevance
“…In our study, no patient died because of urologic complications, and we showed considerably good results (urinary leak rate was 2.5%, stenosis rate was 5%) compared with the literature (2.5%-25%). [12][13][14][15] Decreased blood supply to the donor ureter and faulty surgical techniques are the main causes of urologic complications; however, other problems, such as immunosuppressive drugs and rejections, can cause late obstruction. Although low-dose steroid protocols and meticulous operative techniques tend to reduce incidence or urologic complication, 10 poor ureteral vascularization owing to increased use of expanded criteria donors, especially older individuals, tend to increase this rate.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no patient died because of urologic complications, and we showed considerably good results (urinary leak rate was 2.5%, stenosis rate was 5%) compared with the literature (2.5%-25%). [12][13][14][15] Decreased blood supply to the donor ureter and faulty surgical techniques are the main causes of urologic complications; however, other problems, such as immunosuppressive drugs and rejections, can cause late obstruction. Although low-dose steroid protocols and meticulous operative techniques tend to reduce incidence or urologic complication, 10 poor ureteral vascularization owing to increased use of expanded criteria donors, especially older individuals, tend to increase this rate.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stenoses after renal transplantation may be located at the anastomotic site due to vessel perfusion injury, faulty suture technique, or reaction to suture material, or distally to the anastomosis due to rejection, turbulent flow from kidney malposition, arterial twisting, kinking, and compression (23)(24)(25)(26). Excessive traction of the graft artery during the harvesting, cannulation for transplant perfusion, or a surgical clamp may cause endothelial injury, intimal tears, and vascular dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al found a significantly higher incidence of ACR in their TRAS group compared to controls (0.67 vs 0.35 episodes per patient) with significantly poorer patient and graft survival [7]. Acute rejection was also found to occur more frequently in patients with TRAS (48%) compared to the non TRAS group (27%), although the difference was insignificant [9].…”
Section: Acute Cellular Rejection (Acr)mentioning
confidence: 93%